2022
DOI: 10.3389/fnut.2022.922824
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity profiles with type 2 diabetes in Chinese adults: Findings from the China health and nutrition survey

Abstract: AimsTo examine longitudinal associations of obesity profiles, continuous BMI, and waist circumference (WC) with the risk of type 2 diabetes in Chinese adults.MethodsData were derived from three waves (2009, 2015, and 2018) of the China Health and Nutrition Survey, and 3,595 adults aged 18–65 years who participated in at least two waves of the survey and had completed data were analyzed. Obesity profiles included BMI- or WC-related single obesity and combined obesity. Combined obesity was categorized into six g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…We did not find any significant differences between BMI or CW between individual with normal levels and those with deficient/insufficient levels of vitamin D according with other studies in adults 21,22 . Khader et al in Jordan used sample of adults aged >18 years and reported no significant statistical association between vitamin D levels and the metabolic syndrome components such as CW and BMI 23 .…”
Section: Discussionsupporting
confidence: 48%
“…We did not find any significant differences between BMI or CW between individual with normal levels and those with deficient/insufficient levels of vitamin D according with other studies in adults 21,22 . Khader et al in Jordan used sample of adults aged >18 years and reported no significant statistical association between vitamin D levels and the metabolic syndrome components such as CW and BMI 23 .…”
Section: Discussionsupporting
confidence: 48%